Kontribusi Hutan Rakyat terhadap Pendapatan Petani di Desa Buana Sakti Kecamatan Batanghari Kabupaten Lampung Timur - Lina Nur Aminah; Rommy Qurniati; Wahyu Hidayat (Jurnal Sylva Lestari, 2013)
This study objective is to determine the contribution of private forest management on farmers total income. This study was conducted in March-May 2012 in the Buana Sakti Village, Sub District of Batanghari, District of Lampung Timur. The number of respondent of this study were 40 private forest farmers. Data were collected by direct field observation, interview, and literature review. Data were then analyzed using qualitative and quantitative analysis methods. The results revealed that the average area of private forest owned by farmers were 0,98 ha. The private forest were managed by monoculture, polyculture and agroforestry system. In monoculture system the farmers planted Acacia mangium, in polyculture system the farmers planted Acacia mangium and Hevea brasiliensis while in agroforesty system the farmers combine their land with Acacia mangium, with honey enterprises. The results showed that private forest contribute Rp 17.619.649 every year (70,54%) of the total farmers household income of Rp 24.984.774 every year. Keywords: contributions, farmers income, private forest